Stabilizing n-type hetero-junctions for NiOx based inverted planar perovskite solar cells with an efficiency of 21.6%. Issue 4 (3rd January 2020) - Chen, Wei; Pang, Guotao; Zhou, Yecheng; Sun, Yizhe; Liu, Fang-Zhou; Chen, Rui; Chen, Shuming; Djurišić, Aleksandra B.; He, Zhubing
Abstract : We demonstrate a substantial suppression of interfacial trap states in inverted PSCs via CdZnSeS QDs, leading to a large efficiency improvement. Abstract : The performance and stability of inverted perovskite solar cells (PSC), in particular, those with stable metal oxide hole transport layers, are limited by the instability of perovskite/electron transport layer heterojunctions. In this work, we demonstrate a successful strategy for passivating and stabilizing the perovskite/electronic transport layer n-type heterojunction in a nickel oxide based inverted planar PSC by using chemically stable inorganic Cd x Zn1− x Se y S1− y quantum dots (QDs). Experimental and theoretical results demonstrate that the defects/traps (unsaturated Pb 2+ and mobile iodine ions) on perovskite surfaces can be substantially suppressed by the QDs, leading to a significant reduction of interfacial recombination and more stable n-type heterojunction. Consequently, a significant enhancement of the open-circuit voltage from 1.075 V to 1.162 V and power conversion efficiency from 19.47% to 21.63% is achieved for the QD passivated perovskite-based devices. We also demonstrate that the stabilized n-type hetero-junction results in a dramatic improvement of long-term and operational device stability. Our work demonstrates an effective and simple way to stabilize the perovskite/electron transport layer interface to develop high efficiency stable inverted planar PSCs, which will bring these devices closer to future commercial applications.